Uji Diagnostik Jamur Dermatofita Pada Luka Kaki Penderita Diabetes Melitus dengan Metode PCR (Polymerase Chain Reaction) - Miladiarsi Miladiarsi; Indas Wari Rahman; Santi Santi; Nurfardila Nurfardila (Jurnal Biotek, 2023)
Copyright©2023 Diabetic wounds often occur in people with diabetes mellitus as a result of impaired tissue perfusion and fungal infections, one of which is excessive dermatophytes that cause tissue death. This study aims to detect dermatophyte fungi in foot wounds of diabetics with diabetes mellitus by the Polymerase Chain Reaction (PCR) method. The type of laboratory observational study with a cross sectional study design, and the sampling technique used is total sampling by swab foot wounds in diabetes mellitus patients. The research method uses the PCR method to detect the presence or absence of dermatophyte fungi characterized by the formation of DNA fragments on electrophoresis visualization. The results showed that from 8 samples detected, 5 samples or 62.5% were positive for dermatophyte fungal infection based on amplification results marked by the formation of an amplicon DNA target band measuring around 700-1000 bp using ITS1 primers (forward: 5' GGT TGG TTT CTT TTC CT 3') and ITS2 (reverse: 5' AAG TAA AAG TCG TAA CAA GG 3'), so it can be concluded that in identifying samples using the PCR (Polymerase Chain Reaction) method has a high sensitivity in detecting fungi so as to allow more specific and more accurate results.